MODEL PEMBELAJARAN INKUIRI PADA PERKEMBANGAN BERFIKIR KRITIS SISWA : LITERATURE REVIEW - Halimatus Sa’diyah; Syarifah Aini (Journal of Professional Elementary Education, 2022)
Education aims to prepare students to become a generation that is able to face all the challenges of the times and solve social problems in their environment based on social science concepts that are analyzed scientifically and think critically. The application of the inquiry learning model in the 2013 curriculum through the stages of data collection, analysis, and making hypotheses helps students become people who can think critically scientifically by using social studies concepts. The aim of this study is: a) Knowing the mechanism of the Inquiry Model can be used to improve critical thinking skills in students' social studies learning, b) Knowing how to apply the inquiry model to social studies learning in the classroom, c) Knowing the characteristics of critical thinking, d) Knowing the supporting components of increasing critical thinking skills by applying the inquiry model, and e) Knowing the stages of how to build critical thinking patterns and their effects in improving critical thinking skills by applying the inquiry model. The steps of the Inquiry model are the basis for critical thinking and can be used as a thinking map. The process of reasoning systematically, logically and deeply accompanied by scientific arguments along with evidence in the form of data or accurate information so that conclusions can be obtained that can be accounted for can be used to train critical thinking